Irrationality Measures of Numbers Related to Some $q$-Basic Hypergeometric Series - Väänänen, Keijo (MATHEMATICA SCANDINAVICA, 2014)
We obtain rather good irrationality measures for numbers related to some $q$-basic hypergeometric series. The method uses Padé approximations combined with the iteration of the appropriate functional equation.